"On Fairy-Stories" as a Theory of Literature: Tolkien Meets Ricœur and Girard on the Field of Myth - Gruenler, Curtis A. (Religion & literature, 2023)
Tolkien's essay "On Fairy-stories" implies a general theory of literature that goes beyond the fantasy genre exemplified by his own stories. The more fully developed literary and cultural theories of Paul Ricoeur and René Girard help unfold its implications. What Tolkien terms the "subcreation" of a "secondary world" heightens what, according to Ricoeur, all written works do in projecting a world. The uses Tolkien finds in fantasy, under the headings Recovery, Escape, and Consolation, extend the capacities for knowledge and love of the other valued in many kinds of literature. These uses enrich Girard's emphasis on a conversion of desire mediated by great literature, away from the violent structures served by traditional mythology, so that fantasy clarifies the potential for literature to work as a sort of counter-myth. Tolkien's literary theory, then, supplies what is latent in Ricoeur's projection of a new self in front of the text and of myth as "bearer of possible worlds." The effects Tolkien treasures in the idea of an encounter with Faërie turn out to apply to what all kinds of literature can do.